Grandpa's magic tortilla - Martínez, Demetria, 1960- (Children of the West series., 2010)
When Grandpa Luis's grandchildren are visiting him in Chimayo, New Mexico, they see pictures of animals in one of the tortillas he has cooked for their breakfast.